Sosialiasi dan Pelatihan Penggunaan Aplikasi Orai Kepada Guru Bahasa Inggris Sebagai Media Pembelajaran untuk Meningkatkan Kemampuan Berbicara Bahasa Inggris Siswa Siswi SMP Negeri 4 Laguboti: Pengabdian - Siska Anggita Situmeang; Novra Melisa P.Hutabarat; Jimmi Sitorus; Daniel Binsah Lumbangaol; Palti Hansd Simanjuntak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service (PkM) activity was in the form of Socialization and Training on the use of the Orai application for English teachers at SMP Negeri 4 Laguboti, which aimed to overcome the difficulties teachers had in determining effective speaking learning media, considering that students' English speaking skills were not optimal, even though the Toba region is an international tourist area. The main problem faced by partners was the lack of mastery of technology-based learning media. The solution provided was training on the Orai application, an AI-based digital media for speaking and public speaking practice. The activity, which was held on October 29-31, 2025, included socialization of Orai features such as speed and intonation analysis, followed by direct practice of recording voices and utilizing AI feedback for improvement. The evaluation results showed significant improvements in the aspects of pronunciation, tempo, and clarity of teachers' speech, as well as fostering enthusiasm for integrating technology in the teaching and learning process to make it more interactive and modern.